The NAD(+)-dependent protein deacetylase activity of SIRT1 is regulated by its oligomeric status - Guo, Xiumei (Nature Publishing Group, 2012)
SIRT1, a NAD(+)-dependent protein deacetylase, is an important regulator in cellular stress response and energy metabolism. While the list of SIRT1 substrates is growing, how the activity of SIRT1 is regulated remains unclear. We have previously reported that SIRT1 is activated by phosphorylation at a conserved Thr522 residue in response to environmental stress. Here we demonstrate that phosphorylation of Thr522 activates SIRT1 through modulation of its oligomeric status. We provide evidence that nonphosphorylated SIRT1 protein is aggregation-prone in vitro and in cultured cells. Conversely, phosphorylated SIRT1 protein is largely in the monomeric state and more active. Our findings reveal a novel mechanism for environmental regulation of SIRT1 activity, which may have important implications in understanding the molecular mechanism of stress response, cell survival, and aging.